Analysis of the Effect of Budget Participation on Budgetary Slack: Study Literature Review - Devi Pertiwi Ananda Putri; Sri Trisnaningsih (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this study is to examine how budget participation affects budgetary slack. Using data sources from Mendeley, Publish or Perish 8, and Google Scholar indexed by Sinta 1-6, Google Scholar, Garuda, or EBSCO and Index Copernicus, as well as credible international journals indexed by Scopus throughout a five-year period beginning in 2019–2024, this study employs the System Literature Review approach. The search terms "behavioral aspects," "budget participation," and "budgetary slack" were used to find articles. The study's findings indicate that there is more room for budgetary slack the more people participate in budgeting. Decision-makers have the power to choose the budget's contents when they participate in the budgeting process. However, due to disagreements over ideas or conflicts of interest, including a large number of people in the budget preparation process may increase the likelihood of budget shortages. When it comes to budget participation, everyone has a tendency to search for methods to help the budget targets achieve their goals. In the end, this leads to the practice of raising expenses or lowering them to the appropriate level so that the budget may be met more readily.